Arabic Vocabulary Test Standars for Beginners According to Common European Framework of Reference for Languages (CEFR) - Ihwan Mahmudi; Syifa Firdausi Putri; Diana Fitri Islami; Khansa Nabila; Raihana Nur Azizah (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
Vocabulary is a fundamental component in second language learning, especially for beginners. However, Arabic vocabulary assessment has not been fully standardized according to the Common European Framework of Reference for Languages (CEFR). This study aims to identify vocabulary test criteria for Arabic at the beginner level aligned with CEFR. This research applied a descriptive qualitative method with a literature study approach. Primary data were collected from vocabulary test items in al-Ikhtibârât al-Lughawiyah by Ali Khuly, supported by secondary data on CEFR and language assessment. The results that A1 learners should master approximately 500–600 high-frequency words within themes such as family, time, numbers, daily routines, colors, animals, clothing, weather, and food. Effective test formats include fill-in-the-blank, picture-based multiple-choice, definition-based questions, synonym/antonym tasks, and word usage in context. An ideal proportion of 60% receptive and 40% productive tasks is recommended for beginner-level learners. It is concluded that Arabic vocabulary tests must prioritize validity, reliability, and practicality, while aligning with CEFR for international comparability.